ANALYSIS OF REMEDIAL TEACHING IN BIOLOGY SUBJECT AT CLASS XI SMA NEGERI 1 SEBATIK ACADEMIC YEAR 2022/2023 - Masnia, Masnia; Vlorensius, Vlorensius; Nursia, Nursia (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2024)
Abstract: A crucial part of the entire teaching and learning process is remedial learning. Teachers attempt to assist students in achieving the best possible learning success through remedial programs. The purpose of this study was to examine Remedial Teaching in biology subject at class XI SMA Negeri 1 Sebatik. This study was qualitative and descriptive in nature. Interviews, observations, and documentation were the methods of data collecting used in this study. Data reduction, data display, and conclusion-making were the stages of data analysis. Source triangulation is the method utilized for triangulation to verify the accuracy of the data. One biology teacher from class XI SMA served as the research subject, and purposive sampling was used to select the sample. The studyâ€™s findings demonstrated what biology teacher did when organizing remedial teaching: Biology teacher re-evaluated the situation (made a diagnostic) and chose different courses of action and activities that were not carried out, such as offering assistance and counseling. Regarding the application of remedial teaching: Remedial instruction took place in the classroom. It was time for the End of semester examination (UAS) remedial work to be completed. The group work method was the technique employed. The strategy of the restorative approach was curative. Remedial teaching evaluation involved the teacher summarizing the content to reevaluate learning achievement. Students who had received remedial treatment but were still lacking were given a summary-style reevaluation. Biology teacher only carried out re-diagnoses through observing teaching experiences in each learning process. Â Keywods: Remedial Teaching, Planning, Implementation, Evaluation